Grain of Truth: Unearthing the Factors Contributing to the Financial Strains of Tenant Farmers in the City of Koronadal - Fresco, Christeen Nychole L.; Enrejo, Alyza Khler; Arellano, Rizzamiah M.; Epistola, Rafaelle Andrei A.; Villegas, Nicaila Chelsie P.; Alonzo, Anicka B.; Esmeringa, Khairan Droxx B.; Gaygay Jr. , Carlos F. (Future Science / FSH-PH Publications, 2025)
Filipino farmers endure substantial financial strains despite contributing to the nation's food security. This study described the financial challenges faced by these tenant farmers and their coping mechanisms, aiming to inform interventions for improving their financial well-being and promoting sustainable agricultural practices. The research employed qualitative research conducted in Koronadal City, Philippines, the study engaged eight farmers aged 40 and above with at least five years of farming experience. Purposive sampling, coupled with snowball sampling, facilitated the selection of participants experiencing financial strains and earning 80k or less quarterly. The study sought to determine how the financial strains of the tenant farmers may be described, what factors contribute to their financial strains, how they cope with these challenges, and how effective their coping mechanisms are. Semi-structured guided questionnaires and voice recorders were utilized for data collection, ensuring consistency and transparency. Braun and Clark's (2006) thematic analysis was used to identify key themes from the interview data. Findings reveal pervasive financial challenges stemming from limited access to resources, economic constraints, climate-related disruptions, and predatory pricing practices by agricultural traders. Farmers employ various coping mechanisms, yet their effectiveness remains constrained by systemic barriers. Theoretical frameworks, including Resource-Based Theory, Social Contract Theory, Risk Perception and Communication Theory, and Theory of Religious Coping and Resilience provide a comprehensive lens for understanding these challenges. Ethical considerations were paramount throughout the research process, ensuring participants' autonomy and privacy. This study expands the understanding of the realities faced by Filipino farmers and emphasizes the need for specific measures aimed at improving their financial stability and promoting sustainable farming practices.